Kajian Teknis Lemparan Flyrock pada Pit 303 Jembayan PT Pamapersada Nusantara Distrik Baya Kabupaten Kutai Kartanegara Kalimantan Timur - Asep Triyanda; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. To consider the safe distance of the tool when blasting requires analysis and prediction of flyrock throw. Methods for predicting flyrock throws are Richard & Moore's empirical method and Ebrahim Ghasemi's dimensional analysis. The observation results of the blasting activity were 36 times, and the farthest was 98.87 m of flyrock. The research objective is to analyze the blasting geometry design to better control the flyrock throw, so that the target safe radius of the tool can be reduced from 200 m to 100 m. Prediction of actual flyrock throw using the empirical method Richard & Moore obtained a face burst deviation of 32.68 m, 25.43 m cratering, and 15.12 m rifling, with an error percentage of 69.93%, 30.38%, and 30.64% . Meanwhile, the deviation of Ebrahim Ghasemi's dimensional analysis method is 6.23 m with an error percentage of 9.85%. Based on statistical analysis, stemming has a very strong effect on flyrock throwing, namely 71.40%. Ebrahim Ghasemi's dimensional analysis method is better to predict the actual flyrock throw. To control the actual flyrock throw, a minimum stemming is recommended according to the diameter and depth of the blast hole based on the scaled depth of burial equation, and considering the prediction of a maximum flyrock throw of 50 m and a powder factor not to exceed 0.17 kg / m3. By using these recommendations the safe radius of the tool can be reduced to 100 m with the resulting flyrock safety factor not approaching or exceeding the safe radius of the target, which is 100 m.Keywords: Flyrock, Scaled Depth of Burial, Safe Radius, Stemming